Digital Illustration Fundamentals Vector, Raster, WaveForm, NewMedia with DICF, DAEF and ASNMF - Jackson, Wallace (Apress : Imprint: Apress, 2015)
This concise book covers concepts central to digital illustration using the Inkscape 0.91 open source software package as well as the Adobe Illustrator professional Illustration package. The book builds on the foundational concepts of vector graphics and the SVG format, and gets more advanced as chapters progress, covering what vector new media formats are best for use with Android Studio, Java and JavaFX, iOS, Kindle and HTML5, as well as key factors regarding the data footprint optimization work process, and why data footprint optimization is important. What You Will Learn • What Comprises a digital illustration 2D modeling and rendering pipeline • What are the concepts and principles behind digital illustration content production • How to install and utilize 64-bit Inkscape 0.91 for Windows, Mac OSX and Linux • What are the concepts behind Spline Curves, Strokes, Fills, Patterns and Rendering and how to use and apply them • How to understand and handle digital illustration data formats and data footprint optimization.